2009
DOI: 10.1021/ic802134j
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of Potassium Ferrocyanide Trihydrate as Studied by Solid-State Multinuclear NMR Spectroscopy and X-ray Diffraction

Abstract: The polymorphism of bulk powder samples of potassium ferrocyanide trihydrate (K(4)Fe(CN)(6).3H(2)O, KFCT) has been studied using (1)H, (13)C, and (15)N NMR spectroscopy in combination with X-ray diffraction. At room temperature, KFCT typically crystallizes in a monoclinic C2/c form, which converts irreversibly to a monoclinic Cc form upon cooling below -25 degrees C. The structure of both of these forms has been determined using single-crystal X-ray diffraction. A less common metastable tetragonal I4(1)/a form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 79 publications
4
31
1
Order By: Relevance
“…The presence of two peaks can be explained by the fact that K 4 [Fe II (CN) 6 ]·3H 2 O can crystallize in two crystallographic structures with a slight difference in CN bond lengths. [30] The spectrum of Am III /Fe II exhibits a band at 2069 cm -1 . In comparison with /Fe II , the peak position is shifted to higher energies.…”
Section: Infrared Spectroscopymentioning
confidence: 99%
“…The presence of two peaks can be explained by the fact that K 4 [Fe II (CN) 6 ]·3H 2 O can crystallize in two crystallographic structures with a slight difference in CN bond lengths. [30] The spectrum of Am III /Fe II exhibits a band at 2069 cm -1 . In comparison with /Fe II , the peak position is shifted to higher energies.…”
Section: Infrared Spectroscopymentioning
confidence: 99%
“…This is also supported by in situ observation of their crystallization by optical microscopy, which revealed that the diagonal edge of the octagonal crystals often grew faster than the other edges, transforming the shape into a rectangular one (Figure 2 Table S1 and Figure S3). The SAED data demonstrated that the rectangular and octagonal crystals both correspond to the monoclinic form of KFCT 42 (Figures 6a, 6b and 6c and 6d)., while the hexagonal-shaped crystals are tetragonal (Figure 6e and 6f). 52 Effects of Humidity on Crystals Precipitated in Bulk.…”
Section: Resultsmentioning
confidence: 91%
“…KFCT has a metastable tetragonal form and a thermodynamically stable monoclinic polymorph, and also exhibits a number of twinned crystals. 42,43 Potassium ferrocyanide is used in the food industry to prevent the caking of table salt and to precipitate heavy metals from wine, 44 and has applications as a catalyst, an ion exchanger, photosensitizer and a supramolecular magnetic material. 45,46 KFCT also exhibits a number of unusual solid-state transitions, which have elicited considerable interest from a fundamental point of view.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both redox probes are water soluble and fluorescent. Potassium ferricyanide and potassium ferrocyanide are often used as a tool in physiological experiments [16][17][18]. K3Fe(CN)6…”
Section: Introductionmentioning
confidence: 99%